SpxB Is a Suicide Gene of Streptococcus pneumoniae and Confers a Selective Advantage in an In Vivo Competitive Colonization Model - Regev-Yochay, Gili (American Society for Microbiology, 2007)
The human bacterial pathogen Streptococcus pneumoniae dies spontaneously upon reaching stationary phase. The extent of S. pneumoniae death at stationary phase is unusual in bacteria and has been conventionally attributed to autolysis by the LytA amidase. In this study, we show that spontaneous pneumococcal death is due to hydrogen peroxide (H(2)O(2)), not LytA, and that the gene responsible for H(2)O(2) production (spxB) also confers a survival advantage in colonization. Survival of S. pneumoniae in stationary phase was significantly prolonged by eliminating H(2)O(2) in any of three ways: chemically by supplementing the media with catalase, metabolically by growing the bacteria under anaerobic conditions, or genetically by constructing ΔspxB mutants that do not produce H(2)O(2). Likewise, addition of H(2)O(2) to exponentially growing S. pneumoniae resulted in a death rate similar to that of cells in stationary phase. While ΔlytA mutants did not lyse at stationary phase, they died at a rate similar to that of the wild-type strain. Furthermore, we show that the death process induced by H(2)O(2) has features of apoptosis, as evidenced by increased annexin V staining, decreased DNA content, and appearance as assessed by transmission electron microscopy. Finally, in an in vivo rat model of competitive colonization, the presence of spxB conferred a selective advantage over the ΔspxB mutant, suggesting an explanation for the persistence of this gene. We conclude that a suicide gene of pneumococcus is spxB, which induces an apoptosis-like death in pneumococci and confers a selective advantage in nasopharyngeal cocolonization.